Implementation of International Legal Principles for Judicial Remedy Of Participants in Economical Relations as a Warranty for Sustainable Development of Ukraine - Koverznev, Vadym (European Journal of Sustainable Development, 2019)
The article systemizes the Fundamental principles for activity of judicial authorities, which are formulated in different leading international acts and discovers their legal essence. It is proved that the implementation of the international legal principles of the judicial remedy in the national legislation of Ukraine is a warranty not only to ensure the proper protection of the rights for participants in economic relations but also the sustainable development of the entire state. The author of the article analyzes the progress in implementation of the international legal principles of judicial remedy in the national legislation of Ukraine within the framework of judicial and legal reform, which was conducted in 2016, and sets out the proposals, aimed at improving the situation in the field of extrajudicial dispute settlement (mediation). Keywords: principles of judicial remedy, sustainable development, participant in economical relations, access to court, independent court, fair trial, effectiveness of judicial protection, mediation.